2021
DOI: 10.1080/00365513.2021.1904283
|View full text |Cite
|
Sign up to set email alerts
|

Using blood calprotectin as a measure of blood neutrophils

Abstract: Presently, bed-side or at home quantification of neutrophils in blood (b-neutrophils) is not practical, because cytometric methods are too expensive and technically demanding. We have explored whether calprotectin concentration in whole blood (b-calprotectin) might be a valid measure of b-neutrophils because this principle might be used in a simple and robust immunoassay device. We obtained heparin blood samples from 77 patients with possible neutropenia, most of them cancer patients treated with cytostatic dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Cathelicidins are known as antimicrobial effector molecules characteristic for innate immune response and have been described in humans as biomarker for joint infection predominantly expressed by neutrophils [ 36 ]. Protein S100A8, contained in calprotectin, is reported to be a reliable blood marker for neutrophils [ 37 ]. Myeloid antimicrobial peptide (Map-34) is another effector molecule with anti-microbial properties, which was significantly upregulated in adult samples.…”
Section: Resultsmentioning
confidence: 99%
“…Cathelicidins are known as antimicrobial effector molecules characteristic for innate immune response and have been described in humans as biomarker for joint infection predominantly expressed by neutrophils [ 36 ]. Protein S100A8, contained in calprotectin, is reported to be a reliable blood marker for neutrophils [ 37 ]. Myeloid antimicrobial peptide (Map-34) is another effector molecule with anti-microbial properties, which was significantly upregulated in adult samples.…”
Section: Resultsmentioning
confidence: 99%
“…S100A8/A9 has been identified to be a biomarker in the inflammatory stages of numerous diseases such as ulcerative colitis and acute respiratory infections [34][35][36][37][38][39]. In addition, plasma levels of S100A8/A9 can be a surrogate of blood neutrophil count (below 1 × 10 9 /L) as a cost-effective, easier, and at-home method for monitoring and evaluating patients compared with flow cytometry [40]. Moreover, a study using quantitative protein expression profiling concluded that upregulated S100A8 in serum can be a diagnostic biomarker in two groups of childhood leukemia (B and T cell acute lymphoblastic leukemia; B and T-ALL) [41].…”
Section: S100a8 and S100a9 As A Biomarker In Hmsmentioning
confidence: 99%
“…In addition, they observed a reduction in FIP1L1-PDGFRα-mediated signaling by decreasing FIP1L1-PDGFRα gene expression in the presence of recombinant S100A8 and S100A9 [63] (Figure 4A). Another group showed that the in vitro administration of human recombinant S100A8/A9 (10,20,40,80, and 100 mg/mL) on Nalm6 leukemia cell line induces an apoptotic effect in a time-and dose-dependent manner (after 24, 48, and 72 h) [64] (Figure 4B). A study by Kim et al also revealed the pro-apoptotic effect of S100A8 and/or S100A9 (10 ug/mL for 48 and 72 h) on human monocytic leukemia cells (THP-1) which express high levels of TLR-4 [65] (Figure 4C).…”
Section: Role Of S100a8 and S100a9 In The Treatment Of Hmsmentioning
confidence: 99%